The rhizobacterium Variovorax paradoxus 5C-2, containing ACC deaminase, promotes growth and development of Arabidopsis thaliana via an ethylene-dependent pathway - Chen, Lin (Oxford University Press, 2013)
Many plant-growth-promoting rhizobacteria (PGPR) associated with plant roots contain the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase and can metabolize ACC, the immediate precursor of the plant hormone ethylene, thereby decreasing plant ethylene production and increasing plant growth. However, relatively few studies have explicitly linked ethylene emission and/or action to growth promotion in these plant–microbe interactions. This study examined effects of the PGPR Variovorax paradoxus 5C-2 containing ACC deaminase on the growth and development of Arabidopsis thaliana using wild-type (WT) plants and several ethylene-related mutants (etr1-1, ein2-1, and eto1-1). Soil inoculation with V. paradoxus 5C-2 promoted growth (leaf area and shoot biomass) of WT plants and the ethylene-overproducing mutant eto1-1, and also enhanced floral initiation of WT plants by 2.5 days. However, these effects were not seen in ethylene-insensitive mutants (etr1-1 and ein2-1) even though bacterial colonization of the root system was similar. Furthermore, V. paradoxus 5C-2 decreased ACC concentrations of rosette leaves of WT plants by 59% and foliar ethylene emission of both WT plants and eto1-1 mutants by 42 and 37%, respectively. Taken together, these results demonstrate that a fully functional ethylene signal transduction pathway is required for V. paradoxus 5C-2 to stimulate leaf growth and flowering of A. thaliana.